2017
DOI: 10.1002/pd.5059
|View full text |Cite
|
Sign up to set email alerts
|

Fetal brain injury in complicated monochorionic pregnancies: diagnostic yield of prenatal MRI following surveillance ultrasound and influence on prognostic counselling

Abstract: Prenatal magnetic resonance imaging resulted in changed prognostic counselling in 5/33 pregnancies. Evaluation of incorporation of pMRI into routine surveillance of complicated monochorionic gestations is needed. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…MRI is only performed when ultrasound scans show brain abnormalities. Some recent studies have shown the added value of MRI over ultrasound in the detection of cerebral injury in the context of TTTS [28,29]. However, the evidence is insufficient to confirm a predictive value of fetal MRI for long-term NDI, as this was never studied in large groups.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is only performed when ultrasound scans show brain abnormalities. Some recent studies have shown the added value of MRI over ultrasound in the detection of cerebral injury in the context of TTTS [28,29]. However, the evidence is insufficient to confirm a predictive value of fetal MRI for long-term NDI, as this was never studied in large groups.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-group analysis demonstrated that in MC twin pregnancies, those with anthe sIUFD <28 weeks were significantly more likely to have a co-twin IUFD than those with anthe sIUFD ≥28 weeks. The pathologies of TTTS and IUGRFGR were not associated with an increased risk of co-twin IUFD ( (18,26,29,38,46,48). Ultrasound "missed" 6/19 (31.5%) lesions detected on fMRI in 3 studies (29,38,46) and the other 3 studies demonstrated concordance between the two imaging modalities (18,26,48), although this difference was not statistically significant.…”
Section: Sub-groupmentioning
confidence: 96%
“…The pathologies of TTTS and IUGRFGR were not associated with an increased risk of co-twin IUFD ( (18,26,29,38,46,48). Ultrasound "missed" 6/19 (31.5%) lesions detected on fMRI in 3 studies (29,38,46) and the other 3 studies demonstrated concordance between the two imaging modalities (18,26,48), although this difference was not statistically significant. In abnormal postnatal brain imaging, it was not possible to perform sub-group analysis based on the imaging modalities of MRI or CT scan as 2 studies used ultrasound and MRI (43,48), 1 study used ultrasound and CT (32), and 2 studies did not state the mode of imaging (31,44).…”
Section: Sub-groupmentioning
confidence: 96%
“…Fetal and neonatal MRI studies have shed more light on brain abnormalities detected in TTTS in the last decade. Several studies have reported additional findings of MRI compared to ultrasonography alone, including polymicrogyria and other migrational disorders, sinovenous thrombosis, and more subtle and/or diffuse white matter injury [42,64,[68][69][70][71]. Donors and recipients are equally affected by cerebral injury, although the occurrence of cerebral arterial stroke seems to be a specific risk for recipients [42,62,72].…”
Section: Cerebral Injurymentioning
confidence: 99%